Development and evaluating content validity of CSAI tools - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Chong, Mei Chan (2021)
The current structured nursing clinical skill assessment checklist are steps driven and soft skills component is fragmented and limited. This study aimed to evaluate the face and content validity of a tool that had been developed to assess the current structured clinical skill assessment for Malaysian undergraduate nursing programme. The face and content validity of the instrument were examined based on the opinions of experts. The item content validity index (I-CVI) and scale content validity index (S-CVI) were calculated by adopting the mean approach and inter-rater agreement. The scale was revised based on comments from a panel of five experts in the first review stage, and thereafter, evaluated by another group of four experts in the second review stage. The findings at the face validity stage yielded 10 domains with 8 nursing core procedures being retained, based on 95 percent or more agreement from expert responses. The content validity of the instrument was assessed by S-CVI/UA and S-CVI/Ave, yielding scores of 0.95 and 0.97 respectively. Findings indicated that this instrument had excellent face and content validity to assess the structured clinical skill assessment for Malaysian undergraduate nursing programme.